KERAGAAN INBRIDA PADI SAWAH IRIGASI DI KABUPATEN MUSI RAWAS PROPINSI SUMATERA SELATAN (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2021)
Accelerating the dissemination of several new high-yielding varieties of Inpari through assessments needs to be carried out in the province of South Sumatra. The study aims to determine the yield performance of Inpari 15, Inpari 20, Inpari 22, and Ciherang varieties and to determine the contribution of yield components to yield. The assessment was carried out in May-September 2015 in Musi Rawas Regency (MURA), South Sumatra. The introduced varieties were Inpari 15, Inpari 20, Inpari 22, and the existing farmer varieties (Ciherang). Urea, SP 36, KCl, and manure were used 250, 150, 150 and 500 kg/ha. The variables observed were plant height, number of productive tillers/clumps, length of panicle, number of filled grain/panicle, the weight of 1000 grains, and yield/ha. The results of the study showed that the yields of Inpari 15 (6.48 t/ha), Inpari 20 (7.30 t/ha), Inpari 22 (7.52 t/ha, Ciherang (5.48 t/ha). The yield of Inpari was 18.25-37.23% higher than that of the Ciherang variety. The superiority of the Inpari yield was supported by the number of productive tillers/clumps and the number of grain/panicles which were more than Ciherang. Inpari 15, Inpari 20, and Inpari 22 have the potential to be developed in the MURA Regencyto replace the Ciherang variety.Keyword: Inbred, Paddy, Irrigated Rice